ANTIOXIDANT ACTIVITY, DEXTROSE EQUIVALENT, TOTAL DISSOLVED SOLIDS, AND VISCOSITY OF MALTED RED RICE MILK AT DIFFERENT ENZYME CONCENTRATIONS - Yoga Pratama; Dina Yulia Anggraeni; Yasmin Aulia Rachma; Lita Lusiana Surja; Siti Susanti (Jurnal Penelitian Pascapanen Pertanian, 2021)
Rice milk is a plant-based milk-like product that can be an alternative for people who have an allergy to bovine milk and lactose intolerance. Malting and enzymatic hydrolysis can bring out the natural sweetness of the rice milk product and thus minimize the use of sweeteners. The current research aimed to determine the total value of dissolved solids, viscosity, dextrose equivalent, and antioxidant activity in malted red rice milk with the addition of glucoamylase at different concentrations. The red rice was malted for 48 hours before drying and milling. The resulted malt powder was then diluted and added with glucoamylase enzyme at the concentration of 0%, 1%, 2%, and 3%. Enzymatic hydrolysis occurred at 60°C for 3 hours. Completely Randomized Design was used for the parameters of total soluble solids, viscosity, and dextrose equivalent while the antioxidant activity parameter was analyzed descriptively. The result showed that the addition of glucoamylase significantly (p<0.05) increased the total soluble solids, viscosity, and dextrose equivalent. The highest values were 9.960 °Brix, 1620 cP, and 1.872 for total dissolved solids, viscosity, and dextrose equivalent, respectively. Increasing antioxidant activity was also observed from 6.094% at 0% glucoamylase to 10.762% at 3% glucoamylase addition.